(untitled) - 1947-; Wallace, Bill; McCue, Lisa. (New York, 1989)
Brother and sister cats are taken in by a family and learn the pleasures and dangers of living alongside humans.
Keywords: Cats; Fiction; Brothers and sisters; Fiction